The Effect of Temperature on the Length of Anesthesia for Prospective Male Tilapia Mothers - Anjarsari, Ria Tri; CNAWP, Rizal Perlambang; Gemaputri, Ariesia Ayuning (Jurnal Manajemen Agribisnis dan Agroindustri, 2023)
This research was conducted at the Jember State Polytechnic on 05 November - 12 November 2022. The aim of this research was to observe the time to faint and the time to recover consciousness by administering different temperatures to obtain the optimal temperature or ideal temperature for prospective male tilapia broodstock. Stunning fish using direct drop is a natural anesthetic technique used in fish transportation. In this study, the temperatures used were 3°C, 5°C, 7°C and 9°C per 10 liters of water. The tilapia fish used were 32 prospective male tilapia parents weighing 250 grams which had been aged for a day before being used as test animals. The results of the study showed that the best treatment was shown by P4 (9°C) with a fainting time of 226.25 seconds and a recovery time of 382.00 (seconds).